Cerebral white matter lesions and post‐thrombolytic remote parenchymal hemorrhage. Issue 4 (26th August 2016) - Curtze, Sami; Putaala, Jukka; Sibolt, Gerli; Melkas, Susanna; Mustanoja, Satu; Haapaniemi, Elena; Sairanen, Tiina; Tiainen, Marjaana; Tatlisumak, Turgut; Strbian, Daniel
Abstract : Objective: Parenchymal hematoma (PH) following intravenous thrombolysis (IVT) in ischemic stroke can occur either within the ischemic area (iPH) or as a remote PH (rPH). The latter could be, at least partly, related to cerebral amyloid angiopathy, which belongs to the continuum of cerebral small vessel disease. We hypothesized that cerebral white matter lesions (WMLs)—an imaging surrogate of small vessel disease—are associated with a higher rate of rPH. Methods: We analyzed 2, 485 consecutive patients treated with IVT at the Helsinki University Hospital. Blennow rating scale of 5 to 6 points on baseline computed tomographic head scans was considered as severe WMLs. An rPH was defined as hemorrhage that—contrary to iPH—appears in brain regions without visible ischemic damage and is clinically not related to the symptomatic acute lesion site. The associations between severe WMLs and pure rPH versus no PH, pure iPH versus no PH, and pure rPH versus pure iPH were studied in multivariate logistic regression models. Results: rPHs were mostly (74%) located in lobar regions. After adjustments, the presence of severe WMLs was associated with pure rPH (odds ratio [OR] = 6.79, 95% confidence interval [CI] = 2.57–17.94) but not with pure iPH (OR = 1.45, 95% CI = 0.83–2.53) when compared to patients with no PH. In direct comparison of pure rPH with pure iPH, severe cerebral WMLs were further associated with higher iPH rates (OR = 3.60, 95% CI = 1.06–12.19). Interpretation: Severe cerebral WMLs were associated with post‐thrombolytic rPH but not with iPH within the ischemic area. Ann Neurol 2016;80:593–599